Growth hormone deficiency in adult survivors of childhood brain tumors treated with radiation - Mette Marie Baunsgaard; Anne Sophie Lind Helligsoe; Louise Tram Henriksen; Torben Stamm Mikkelsen; Michael Callesen; Britta Weber; Henrik Hasle; Niels Birkebæk (Endocrine Connections, 2023)
Objective: Growth hormone deficiency (GHD) is the most common endocrine la te effect in irradiated survivors of childhood brain tumors. This study a imed to determine the prevalence of GHD in adults treated with proton or photon irradiation for a brain tumor in childhood and to detect undiagnosed GHD. Design: This study is a cross-sectional study. Methods: We investigated GHD in 5-year survivors from two health region s in Denmark treated for childhood brain tumors with cranial or craniospinal irradiation in the period 1997–2015. Medical charts were reviewed for endocrinological and other health data. Survivors without a growth hormone (GH) test at final height wer e invited to a GH stimulation test. Results: Totally 41 (22 females) survivors with a median age of 21.7 ye ars (range: 15.1– 33.8 years) at follow-up and 14.8 years (range: 5.1–23.4 years) since diagnosis were included; 11 were treated with proton and 30 with photon irradiation; 18 of 21 survivors were previously found to have GHD; 16 of 20 survivors with no G H test at final height were tested, 8 (50 %) had GHD. In total, 26 of 41 patients (63% ) had GHD. Insulin-like growth factor-1 (IGF-1) is associated poorly with the insulin t olerance test (ITT). Conclusion: This study identified a high prevalence of undiagnosed GHD in s urvivors with no GH test at final height. The results stress the importance of screening for GHD at final height in survivors of childhood brain tumors with prior exposure to cranial irradiation, irrespective of radiation modality and IGF-1. Significance statement: This cross-sectional study reports a prevalence of 63% of GHD in irradiated childhood brain tumor survivors. Furthermore, the study identified a considerable number of long-term survivors without a GH test at final height, of whom, 50% subsequently were shown to have undiagnosed GHD. Additional ly, this study confirmed that a normal serum IGF-1 measurement cannot exclude t he diagnosis of GHD in irradiated survivors. This illustrates the need for improvements in the diagnostic approach to GHD after reaching final height in childhood brain t umor survivors at risk of GHD. In summary, our study stresses the need for GHD testing in all adult survivors treated with cranial irradiation for a brain tumor in childhood irrespe ctive of radiation modality.